Correction: A knowledge, attitude, and practice survey on mediation among clinicians in a tertiary-care hospital in Singapore (PLoS ONE (2018) 13:7 (e0199885) DOI: 10.1371/journal.pone.0199885) - Lin W. (2019)
10.1371/journal.pone.0205451